(Diacetoxyiodo)benzene‐mediated Selective Synthesis of α‐Azido Ketones or Acyl Azides from β‐Keto Acids. Issue 8 (14th June 2018) - Zheng, Zhao‐Jing; Yu, Tian‐Yang; Xu, Peng‐Fei; Wei, Hao
Abstract: (Diacetoxyiodo)benzene‐mediated selective synthesis of α‐azido ketones or acyl azides from keto acids is developed. The selectivity depends on the amounts of the reagents used. Treatment of β‐keto acid derivatives with 1.2 or 2.2 equivalents of (diacetoxyiodo)benzene results in α‐azido ketone or acyl azide products, respectively. Initial mechanistic studies show that monobromomethyl ketone and dibromomethyl ketone are plausible intermediates in these reactions. Abstract : From β‐Keto to α‐azido : (Diacetoxyiodo)benzene‐mediated selective synthesis of α‐azido ketones or acyl azides from keto acids is developed. The selectivity depends on the amounts of reagents used.